Mechanical Regulation of Cardiac Aging in Model Systems. Issue 10 (13th May 2016) - Sessions, Ayla O.; Engler, Adam J.
Abstract : Unlike diet and exercise, which individuals can modulate according to their lifestyle, aging is unavoidable. With normal or healthy aging, the heart undergoes extensive vascular, cellular, and interstitial molecular changes that result in stiffer less compliant hearts that experience a general decline in organ function. Although these molecular changes deemed cardiac remodeling were once thought to be concomitant with advanced cardiovascular disease, they can be found in patients without manifestation of clinical disease. It is now mostly acknowledged that these age-related mechanical changes confer vulnerability of the heart to cardiovascular stresses associated with disease, such as hypertension and atherosclerosis. However, recent studies have aimed at differentiating the initial compensatory changes that occur within the heart with age to maintain contractile function from the maladaptive responses associated with disease. This work has identified new targets to improve cardiac function during aging. Spanning invertebrate to vertebrate models, we use this review to delineate some hallmarks of physiological versus pathological remodeling that occur in the cardiomyocyte and its microenvironment, focusing especially on the mechanical changes that occur within the sarcomere, intercalated disc, costamere, and extracellular matrix.